Influence of calcium concentration on the structural and electrical properties of PZT ceramic - Silva, Margarete S.; Cavalheiro, Alberto A.; Zaghete, Maria A. [UNESP]; Cilense, Mário [UNESP]; Longo, Elson [UNESP]; Cavenago, Gustavo F.; Dias, Rafael G.; Silva, Lucas L.; Motta, Fabiana V. (Trans Tech Publications, 2015)
Lead zirconate titanate, with Zr/Ti ratio of 53/47 was prepared by the polymeric precursor method. The powders were doped with 0, 0.2, 0.4 end 0.6 mol% of Ca2+ and characterized by XRD. The percentages of tetragonal and rhombohedral phases were calculated through Rietveld refinement. A systematic study of the effect of dopant on the ferroelectric and piezoelectric properties of PZT was carried out. The remanent polarization, planar coupling factor and piezoelectric charge constant, increase with dopant concentration.
Keywords: Ca-doped; Piezoelectric properties; PZT